Identifying risk groups for osteoporosis by digital panoramic radiography - Satish Alapati; Reddy Sudhakara Reddy; Ramesh Tatapudi; Ramya Kotha; Naveen Kumar Bodu; Saikiran Chennoju (Wolters Kluwer Medknow Publications, 2015)
Background: Osteoporosis is a disease characterized by low bone mass and microarchitectural deterioration of bone tissue, leading to bone fragility, and enhanced susceptibility to fractures. Dental radiographs, especially panoramic images, have been used to predict bone mineral density. A number of indices, (mandibular cortical index [MCI], mandibular cortical width [MCW], and panoramic mandibular index [PMI]) have been developed to assess and quantify the quality of mandibular bone mass and to observe the signs of resorption. Objectives: The objectives of the study were to assess mental index (MI), MCW index, and PMI with bone density in identifying risk group for osteoporosis and also to investigate influence of age and gender on MI, MCI, and PMI. Materials and Methods: After obtaining consent, details regarding age, gender, systemic health status, and oral parafunctional habits were recorded in each patient. Then a digital panoramic radiograph was taken. The image thus obtained was subjected to calibrations and morphometric analysis using Digora version 2.7. The obtained values of indices were compared with the mean values of indices, to evaluate subjects whether they are prone to osteoporosis or not. The obtained information was subjected to statistical analysis for the significance of the parameters. Results: Data analysis showed that calibration indices were highly significant in the assessment of risk group for osteoporosis than noncalibration index. The subjects at a higher risk for development of osteoporosis were old-aged adults with higher prevalence being reported in women compared to male subjects. Conclusion: In conclusion, our results suggest that higher percentage of subjects with undetected decreased bone mineral density may be identified based on trained general dental practitioners analyses of their panoramic radiographs using simple screening analytical calibration MI and MCI.